YOUTH POLITICAL AND CULTURAL MOVEMENTS AGAINST THE UNITED STATES INVASION IN VIETNAM IN THE 1960S - Agnes Yudita Larasatiningrum (Universitas Gadjah Mada, 2015)
History has shown us that the most successful progressive movements have been intergenerational. Thus, this article will deeply examine about youth movements in the U.S specifically on youth movement against the U.S invasion in Vietnam War around 1960s. Vietnam War was the first modern American conflict that seriously affected the United States not only politically, but also socio-culturally. It will be explored how youth generation has become a breakthrough in American history since it was the most significant movement of its kind in the nation’s history. According to Karl Mannheim one generation is not fully continuity of the elder generation, but they could be different and challenging the established form. Youth tend to reject the US involvement in the Vietnam War because there is a gap between the ideals they have learned from older generations and the realities they have experienced.